Local governance in industrial countries - Shah, Anwar (Public sector governance and accountability series., 2006)
The information revolution, in recent years, has worked as a catalyst to create a globalized yet localized world with local governments playing an ever-increasing role in the domestic and global economy. How these governments will be able to shoulder their responsibilities' especially the delivery of local services more effectively is the concern of this book. The book, edited by Anwar Shah, provides a comparative perspective on international practices in local governance and draws lessons from these experiences to guide future reform. Case studies include the following countries: Argentina, B.